Wireless Sensor Based Monitoring System for Forest Tree Poaching and Fire Using Iot - Arulstephen, C; K. Raghulsharma, R; Ebenezer Abishek, B; Satish Kumar, P (International Journal of Engineering and Technology, 2018)
Forest tree poaching is a serious threat to forest resource and has an impact on the environment hence preservation of trees is aÂ  must for mankind .This paper mainly aims at monitoring the trees using Micro â€“Electro mechanical system(MEMS) technology and employing vibration sensor , sound sensor, fire sensor. The vibration produced while cutting of trees using MEMS accelerometer is sent through Zigbee to the main server and the location is detected using GPS likewise if fire is detected the information is sent through IoT and it can be viewed by forest ranger hence alert message is sent to detect and avoid poaching of trees and fire in forest.Â